2018
DOI: 10.4025/actascitechnol.v40i1.35242
|View full text |Cite
|
Sign up to set email alerts
|

<b>New product development in small and medium-sized technology based companies: a multiple case study

Abstract: The new product development (NPD) becomes more and more critical for the competitiveness, due to increasing internationalization of markets and diversification of products and decreasing life cycle of products. This paper addresses gaps in NPD literature, presenting a multiple case study involving small and medium-sized enterprises (SMEs), all of them are technology-based companies (TBC) manufacturers of electronics. A detailed investigation was conducted and three main sources of data were used for each case:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(43 reference statements)
0
2
0
1
Order By: Relevance
“…Linking NPD situations with tools needed may be a good way for designing the NPD process. In a study of NPD in multiple technology-based SMEs, Salgado, Salomon, Mello, and da Silva [97] identified that tools such as Technology Road mapping (TRM), QFD, Failure Mode and Effect Analysis (FMEA), Design for X (DFX), and others are not being fully utilized, but tools such as CAD and financial analysis are already being used. In an evaluation of product development methodologies of SMEs in metal-mechanic sector, Kaminski, Oliveira, and Lopes [42] identified that CAD and numeric computation software is utilized to support the creation and modification of the product, but PDM/PLM has not been utilized.…”
Section: Process Modeling Tools and Techniquesmentioning
confidence: 99%
“…Linking NPD situations with tools needed may be a good way for designing the NPD process. In a study of NPD in multiple technology-based SMEs, Salgado, Salomon, Mello, and da Silva [97] identified that tools such as Technology Road mapping (TRM), QFD, Failure Mode and Effect Analysis (FMEA), Design for X (DFX), and others are not being fully utilized, but tools such as CAD and financial analysis are already being used. In an evaluation of product development methodologies of SMEs in metal-mechanic sector, Kaminski, Oliveira, and Lopes [42] identified that CAD and numeric computation software is utilized to support the creation and modification of the product, but PDM/PLM has not been utilized.…”
Section: Process Modeling Tools and Techniquesmentioning
confidence: 99%
“…Micro, Small, and Medium Enterprises (MSMEs) play a key role in the marketplace of the economies around the world. While definitions vary from country to country, their impact on battling economic issues such as poverty and unemployment while supporting innovation and growth is recognized in the different regions (Salgado et al, 2018;Scuotto, Santoro et al, 2017). MSMEs impact job creation and economic development (Sahut et al 2019) in a world that's heavily driven by the digitalization (post-COVID-19 pandemic) of both public services and businesses.…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, las categorías difieren entre países y regiones, por lo general, el denominativo de Pymes, se utiliza para hacer referencia a las pequeñas y mediana empresa (Dambiski et al, 2021). Las Pymes han sido reconocidas por su importancia para la economía en diferentes países y regiones (Salgado et al, 2018;Millward and Lewis, 2005;Koufteros et al, 2005;Millward et al, 2006;Mu et al, 2007;Love and Roper 2015;Acs et al, 2017;Maksimov et al, 2017). Sus aportaciones a la generación de empleos a partir de la producción y distribución de bienes y servicios las hace una fuente invaluable para el progreso económico, social y familiar en cualquier país (Salimi and Rezaei, 2018;Scuotto et al, 2017;Soto-Acosta et al, 2015, 2017Kumar and Antony, 2008;Bužavaitė et al, 2019;Schweizer, 2012).…”
Section: Introductionunclassified